A Dél-Dunántúl gazdaságszerkezete és ipara - Hrubi, László (Tér és Társadalom, 1994)
There are no uniform, complete measures for the evaluation of the regional economic structure, but some typical tendencies can serve as a standard in connection with the structural change. Such generally perceptible trends are, for example: the modification of the employment structure towards the secondary, and especially the tertiary sectors, within industry the progress of the manufacturing sector, within industry the weakening of the privileged position of urban settlements, the process of the spatial penetration of new organisations. The economy of Southern Transdanubia as a whole was not given a more important role in the centrally controlled economic development of the previous period. Its "average position", the "semi-shade" situation is still typical as it was in the past. Of course, some sectors or smaller regions of the arca function as development regions, but there naturally followed not mainly regional but sectoral (or macroeconomic) aspects and interests. Their regional impact, though not insigníficant, had only a secondary role. Several areas of the region could often be found in different programmes aimed at the decrease of regional differences. The lack of long-lasting selected (industrial) development strategies protected the arca from sufferíng the apparent collapses taking place after the change of model: there are only rather regional crisis situations, that can be localised, in the county. In the breakdown of the active earners by economic sectors, there were moderate changes in the region in 1980-1990. These changes as a whole did not modify the fundamental structural feature that the region – with the exception of Baranya county – is much more agrarian than the whole of the country. The transition of the economic structure of the Southern Transdanubian region is slow. The transition of the company structure, the adjustment were a bit late, partly because of the inherited, partly because of the present weight, role of the region within the economic potential of Hungary. The appearance of foreign capital is less frequent than the national average, and it affected the smaller units, especially. The change of structure and organisation is the most advanced in the third sector, the dynamics of the transition is slower in industry for the time being, while the selection in agriculture takes place mainly in the counties with less favourable endowments. As a general element of the modification of the industrial structure, the decline of the importance of light industry and the rising of the importance of food processing should be mentioned, besides the existence of the inherited particularities of the industrial structure. It is mainly urban industry, the network of the village industry, with an exception or two, is still less developed than the not very well advanced national level and shows a quite feeble situation. The junctíons of the regional division of labour and co-operation can be called development clusters that create the basis of the regional development strategy. These clusters arc condensation points in the economy of the region that on the one hand mean the chain of economic units with sectoral and functional links (a kind of special vertical connection), by the production of a competitive product or service, profitable productive process, mainly relying on and using the resources of the region, on the other hand, they mean a connected network of the economic-service units of the region, which can directly transmit the market effects, and also provide the inpoformation flow of common interest and the reaction to market impulses, as well. Examining the possible clusters the following fundamental bottle-necks can be seen: one is the lack of the first part of the linkage that can be called an innovation system in the narrower sense: both the product- and the technology development are extremely underdeveloped in Southern Transdanubia; the other is the basic lack at the end of the linkage , the lack of marketing apparatus, which causes fundamental development problems in two directions, in the organisation of sales and the acquisition of market information. Analysing the possible main junctions, clusters of the development of the region, a basic particularity is the fact that there is no cluster (and in the foreseeable future there is not going to be) that could be the most particular feature of the economy of the region and could give the regional development a face. Thus the economic development of the region can take place on the basis of a potential with diverse structure. Industry will not lose importance, although its role in the employment will be less emphasised. Since within industry, food processing is a possible development junction, a great decrease in the role of agriculture cannot be predicted, either. The only new element of the structural modification can be tertialisation.